Adoption of Integrated forms of Support for Family-Provided Care of Senior Citizens in a Selected Location in the Czech Republic (Journal of Intellectual Disability - Diagnosis and Treatment, 2013)
The primary focus of this paper is to outline how integrated forms of support are applied to unofficial care providers who provide care of senior citizens in the administrative region of Písek – a municipality with extended area of operation. The result of the quantitative survey provides information on how families who provide care to senior citizens in their natural home environment make use of the possibilities of professional health and social support provided in the territory of the respective self-administration entity. Also, the survey reveals what services would ease work for these unofficial care providers. The survey was done from 8/2010 to 11/2011 with 475 unofficial care providers. The outcome of the survey is the need for extending the professional services provided to smaller municipalities and rural agglomerations, so that “dead spots” in the Písek region can be filled.